2011
DOI: 10.1021/nl203235u
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hot-Carrier Cooling and Ultrafast Spectral Diffusion in Strongly Coupled PbSe Quantum-Dot Solids

Abstract: PbSe quantum-dot solids are of great interest for low cost and efficient photodetectors and solar cells. We have prepared PbSe quantum-dot solids with high charge carrier mobilities using layer-by-layer dip-coating with 1,2-ethanediamine as substitute capping ligands. Here we present a time and energy resolved transient absorption spectroscopy study on the kinetics of photogenerated charge carriers, focusing on 0-5 ps after photoexcitation. We compare the observed carrier kinetics to those for quantum dots in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 37 publications
(64 reference statements)
9
95
1
Order By: Relevance
“…Both are likely to occur simultaneously in NC solids (e.g., trapmediated recombination). Here, we assume that the decrease in photoconductivity is well-modeled by the recombination of electronÀhole pairs because carrier relaxation is rapid 21,52 and both recombination and trapping of charge carriers ; removal from highmobility states ; have similar results on the effective carrier concentration and the terahertz transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Both are likely to occur simultaneously in NC solids (e.g., trapmediated recombination). Here, we assume that the decrease in photoconductivity is well-modeled by the recombination of electronÀhole pairs because carrier relaxation is rapid 21,52 and both recombination and trapping of charge carriers ; removal from highmobility states ; have similar results on the effective carrier concentration and the terahertz transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5a depicts the quantity S(t) = Φ e (t)μ e + Φ h (t)μ h , as a function of time, t, after photoexcitation, which is the sum of the product of the quantum yield of electrons, Φ e (t) and holes, Φ h (t), and the real mobility component of their mobility, (μ e and μ h ). At early times, the real THz conductivity exhibits a fast decay at times ≤ 4 ps, which is assigned to relaxation of highly mobile hot charges to the band edge, where the mobility is lower [7,[22][23][24]. After 4 ps, S(t) is as high as 20 ± 2 cm 2 /Vs.…”
Section: Terahertz (Thz) Spectroscopy/conductivitymentioning
confidence: 99%
“…For example, the increased interparticle coupling and greater electrical conductivity previously demonstrated in these SCN exchanged samples 13 likely increase exciton and charge carrier diffusion to lower energy QDs. 27 Recent room temperature studies of QD solids demonstrated that excitons can become concentrated at low energy "hotspots", enabling multiexciton phenomena when excitation densities surpass a rather low threshold of 10 À3 excitons per quantum dot. 66 Under these conditions, which are met in this study, Auger processes can produce fast, radiationless recombination as well as hot carrier generation that enhances the likelihood of carrier trapping.…”
Section: Resultsmentioning
confidence: 99%